Fetomaternal outcome in pregnant women with epilepsy in a tertiary care hospital: a retrospective study - Ajitha, Kolakotla; R., Sheela S.; S., Nandini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Epilepsy is the second common chronic neurological disorder complicating pregnancy after migraine. Incidence of seizure disorder in women attending antenatal clinics is estimated to be 0.3-0.5% of all births. These pregnancies are a challenge to patient and clinician, the double burden of seizures and the antiepileptic drugs (AED) exposure are responsible for the poorer outcome of infants. The aim of the study is to analyse the fetal and maternal outcome in pregnancies that are complicated by epilepsy. Methods: This was a single centre retrospective study on pregnant women with epilepsy at a tertiary care centre from the period of 01st August 2021 to 1st August 2024. The data of all booked antenatal patients diagnosed with epilepsy was collected from the labour records and electronic medical records. Details included in the study were preconceptionally counselling, age, parity, gestational age at the time of delivery, age of onset of epilepsy, duration of epilepsy, seizure during pregnancy, antiepileptic drug usage in pregnancy, maternal complications and fetal outcomes. Results: Out of the total 6400 deliveries over in our institution I identified 54 patients with epilepsy complicating pregnancy thus giving a incidence of 0.84 %. Majority of patients were in the age group of 20-30 years . Having a duration of seizures more than 10 years. 87.03 % of patient had GTCS type of seizure and 68.51% of patient gave a history of seizure free period prior to pregnancy. 24.07 % of patients had incidence of antepartum seizures, though most of the patients didn’t need any change in dose or medication. Even with the episodes of antepartum seizures 83.34% of females had a term delivery, 59.25 % patients had a normal delivery and 59.25 % of babies were >2.5 kg at the time of birth. Only 1 child was born with congenital anomalies and 25.92% children required NICU admission. Conclusions: In this study we observed that though pregnancy with epilepsy needs comprehensive antenatal care and this results in uneventful pregnancies with good feto-maternal outcome.